Singlet fission dynamics and optical spectra of pentacene and its derivatives - Sun, Kewei (2021)
A multimode Brownian oscillator model is employed to investigate the absorption spectra of pentacene and its derivatives in solution and thin films. Excellent agreement has been obtained between simulated and measured absorption spectra. Furthermore, using parameters obtained from fitting the absorption spectra of these pentacene derivatives, the singlet fission dynamics and two-dimensional electronic spectra of an ab initio Hamiltonian are investigated by Dirac–Frenkel time-dependent variation with multiple Davydov trial states. It is found that the periodic wave packet motion induced in the displaced excited state, and the accompanying vibrational relaxation, can be visualized by two-dimensional electronic spectra at short times.